Fuel‐Free Nanocap‐Like Motors Actuated Under Visible Light. (15th January 2018) - Wang, Xu; Sridhar, Varun; Guo, Surong; Talebi, Nahid; Miguel‐López, Albert; Hahn, Kersten; van Aken, Peter A.; Sánchez, Samuel
Abstract: The motion of nanomotors triggered by light sources will provide new alternative routes to power nanoarchitectures without the need of chemical fuels. However, most light‐driven nanomotors are triggered by UV‐light, near infrared reflection, or laser sources. It is demonstrated that nanocap shaped Au/TiO2 nanomotors (175 nm in diameter) display increased Brownian motion in the presence of broad spectrum visible light. The motion results from the surface plasmon resonance effect leading to self‐electrophoresis between the Au and TiO2 layers, a mechanism called plasmonic photocatalytic effect in the field of photocatalysis. This mechanism is experimentally characterized by electron energy loss spectroscopy, energy‐filtered transmission electron microscopy, and optical video tracking. This mechanism is also studied in a more theoretical manner using numerical finite‐difference time‐domain simulations. The ability to power nanomaterials with visible light may result in entirely new applications for externally powered micro/nanomotors. Abstract : A cap‐shaped Au/TiO2 nanomotors are presented that show enhanced Brownian motion under visible light in water in a fuel‐free manner. The motion results from the surface plasmon resonance effect leading to self‐electrophoresis between the Au and TiO2 layers. This mechanism is named plasmonic photocatalytic effect, demonstrated experimentally and by finite‐difference time‐domain simulations.